SAE Technical Paper Series 2010
DOI: 10.4271/2010-22-0015
|View full text |Cite
|
Sign up to set email alerts
|

Structural Response of Cadaveric Ribcages Under a Localized Loading: Stiffness and Kinematic Trends

Abstract: To improve understanding of structural coupling and deformation patterns throughout the loaded ribcage, the present study reports the force-displacement and kinematic responses under a highly-localized loading condition using three PMHS ribcages (ages 44, 61, and 63 years). The ribcages were quasi-statically loaded locally to a non-failure displacement (nominally 15% of the ribcage depth at the loaded rib level) at approximately 25 unilateral locations and 5-7 geometrically symmetric bilateral locations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Field data analyses, computer simulations and cadaver tests have all shown that the incidence of AIS 2+ thoracic injuries increased with age (Carter et al, 2014;Ridella et al, 2012;Zhou et al, 1996). The risk of ribcage injuries in crashes also differs significantly between men an women (Bellemare et al, 2003;Cerney and Adams, 2004;Kimpara et al, 2005;Kindig et al, 2010). In particular, the risk of being seriously injured in crashes is higher for women than men (Bose et al, 2011;Parenteau et al, 2013), and the increase of thoracic injury risk with age is greater for women than men (Carter et al, 2014;Parenteau et al, 2013;Ridella et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Field data analyses, computer simulations and cadaver tests have all shown that the incidence of AIS 2+ thoracic injuries increased with age (Carter et al, 2014;Ridella et al, 2012;Zhou et al, 1996). The risk of ribcage injuries in crashes also differs significantly between men an women (Bellemare et al, 2003;Cerney and Adams, 2004;Kimpara et al, 2005;Kindig et al, 2010). In particular, the risk of being seriously injured in crashes is higher for women than men (Bose et al, 2011;Parenteau et al, 2013), and the increase of thoracic injury risk with age is greater for women than men (Carter et al, 2014;Parenteau et al, 2013;Ridella et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rib 1, which is attached to both the sternum and the clavicle, plays a major role in load-sharing through the ribcage [59], and (although rare) can be fractured during severe trauma or physical stress [60][61][62][63][64] or surgery [65]. Preliminary testing suggests that the proposed model would capture rib 1 geometry with accuracy comparable to ribs 2-10.…”
Section: Futurementioning
confidence: 96%
“…Quasi-static point loading of the ribcage was simulated, using the method outlined in Kindig et al (2010). In that study, isolated eviscerated ribcages mounted upright from three PMHS were quasi-statically loaded by a plate interfacing with a spherical segment glued to the superficial surface of the ribs.…”
Section: Point Loading Of the Eviscerated Ribcagementioning
confidence: 99%
“…(a) Scaled force-scaled displacement, (b) CORA ratings. Experimental corridors are adapted fromKindig et al (2010).…”
mentioning
confidence: 99%